1991
DOI: 10.1002/mus.880141210
|View full text |Cite
|
Sign up to set email alerts
|

High pancuronium sensitivity of axonal nicotinic‐acetylcholine receptors in humans during organophosphate intoxication

Abstract: The effect of low-dose pancuronium on neuromuscular transmission was studied in 2 patients during the early and late stages of severe organophosphate intoxication. Single evoked compound muscle action potentials (CMAP) were followed by repetitive discharges and a decrement-increment (D-I) phenomenon with 10-, 20-, and 50-Hz supramaximal nerve stimulation. Intravenous pancuronium, 1 mg, abolished the D-I phenomenon, while the repetitive discharges of the CMAP were only partially reduced. It is postulated, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…There is a rapid onset of difficulty in breathing associated with the use of the accessory muscles of respiration and, if untreated, death follows rapidly as a result of ventilatory [23,62]. The decrement response seen initially during the intermediate syndrome is similar to TOF fade and tetanic fade, which is usually attributed to a decrease in the effectiveness of the presynaptic cholinergic feedback mechanism and is associated with partial or recovering nondepolarising block.…”
Section: The Intermediate Syndrome [60]mentioning
confidence: 99%
See 2 more Smart Citations
“…There is a rapid onset of difficulty in breathing associated with the use of the accessory muscles of respiration and, if untreated, death follows rapidly as a result of ventilatory [23,62]. The decrement response seen initially during the intermediate syndrome is similar to TOF fade and tetanic fade, which is usually attributed to a decrease in the effectiveness of the presynaptic cholinergic feedback mechanism and is associated with partial or recovering nondepolarising block.…”
Section: The Intermediate Syndrome [60]mentioning
confidence: 99%
“…The repetitive firing following a single evoked compound muscle action potentials is considered to be due to excessive acetylcholine in the presence of an anticholinesterase, causing antidromic firing due to stimulation of the axonal (presynaptic) nicotinic receptors [66]. Besser et al [23] showed that pancuronium 1 mg, which acts both pre-and postsynaptically, abolished the D-I phenomenon and partially reduced the repetitive discharge of the compound muscle action potentials in two patients with OP poisoning [23].…”
Section: The Intermediate Syndrome [60]mentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Consistently, patients exposed to organophosphate poisoning are more sensitive than resistant to pancuronium. 45 The increased sensitivity to atracurium in our studies reflects the decreased margin of safety of neurotransmission induced by pyridostigmine, either due to its direct allosteric interaction with the acetylcholine receptors, or due to desensitization of acetylcholine receptors by acetylcholine. 17 Our observation that the dose-response curves of atracurium can indeed shift to the left is in agreement with the clinical scenario, where chronic cholinesterase inhibition induced by organophosphate poisoning made patients more sensitive to nondepolarizers.…”
Section: Critical Care Medicinementioning
confidence: 63%
“…Decremental response to repetitive nerve stimulation dramatically worsened after injection of edrophonium (Maselli et al, 1986), indicating the effects of a further excess of acetylcholine, whereas the administration of pancuronium improved neuromuscular transmission, indicating a blockade of nicotinic receptors (Besser et al, 1990(Besser et al, , 1991. Distinction between these findings and those detected during the intermediate syndrome may be difficult (see Section 72.2.3.2).…”
Section: Routine Hematological and Biochemical Testsmentioning
confidence: 99%